Factorial validation of the Attitudes toward Women Scale for Adolescents (AWSA) in assessing sexual behaviour patterns in Bolivian and Ecuadorian adolescents - Lina Jaruseviciene; Sara De Meyer; Peter Decat; Apolinaras Zaborskis; Olivier Degomme; Mildrett Rojas; Salazar Arnold Hagens; Nancy Auquilla; Bernardo Vega; Anna C. Gorter; Miguel Orozco; Jeffrey V. Lazarus (Taylor & Francis Group, 2014)
Background: Adolescents' health is greatly influenced by social determinants, including gender norms. Although research has shown that there is an association between gender attitudes and adolescents' sexual behaviour, few studies have assessed this relationship carefully. The Attitudes toward Women Scale for Adolescents (AWSA) is widely used to assess gender attitudes among adolescents; however, to our knowledge it has not been applied in Latin America. Objective: To apply AWSA in Latin America for the first time, to perform a factorial validation of this scale and to assess the relationship of gender attitudes and sexual behaviour in Bolivian and Ecuadorian adolescents. Design: This cross-sectional study was carried out in 2011 among 14-18 year olds in 20 high schools in Cochabamba (Bolivia) and six in Cuenca (Ecuador) as a part of a larger project. Schools were purposively selected. A Spanish version of the 12-item AWSA was employed for this study. The assessed aspects of adolescent sexual behaviour were: reported sexual intercourse, reported positive experience during last sexual intercourse and reported current use of contraception. The psychometric properties of AWSA were investigated, and both explanatory and confirmatory factorial analyses were performed. Results: The number of questionnaires included in the analysis was 3,518 in Bolivia and 2,401 in Ecuador. A factorial analysis of AWSA resulted in three factors: power dimension (PD), equality dimension (ED) and behavioural dimension (BD). ED showed the highest correlates with adolescent sexual behaviour. Higher scores of this dimension were associated with a more positive experience of sexual relationships, a higher current use of modern contraception and greater sexual activity among girls. Conclusions: This study revealed a three-factorial structure of AWSA and demonstrated that by employing factors, the sensitivity of AWSA increases as compared to using the scale as a whole to assess sexual behaviour. This could have important implications for future research on gender and the sexual experiences of adolescents.